2017
DOI: 10.1007/s00251-017-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the variants of the L-ficolin gene (FCN2) in the arctic populations of East Siberia

Abstract: L-ficolin encoded by FCN2 gene is a crucial factor of defense against infection in humans. We studied the prevalence of the two common variants (rs17549193 and rs7851696) in aboriginal and alien populations of the Taymyr-Dolgan-Nenets Region of Krasnoyarskiy Kray, East Siberia, Russia (Nenets, Dolgans, Nganasans, Russians). We found a decreased prevalence of the rs17549193*T allele in all aboriginal populations as compared to Russians. Also, its frequency was the lowest in the Nenets among the studied populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 16 publications
0
12
0
13
Order By: Relevance
“…As mentioned above, currently, the population frequencies of mutations associated with congenital deficiency of H-ficolin and MASP-2 in Russian populations as a whole, and in populations of indigenous peoples of the Russian Arctic regions in particular, have not been previously studied. Moreover, the previously identified features of the genetic regulation of lectin pathway proteins of complement activation in newborns of the Taimyr Dolgan-Nenets region of the Krasnoyarsk Territory have shown the indigenous populations of the Arctic to be genetically characterized by greater activity of at least two different lectin pathway components of complement activation, i. e. MBL and L-ficolin, indicating a high tone of the lectin pathway of complement activation in general (Smolnikova et al, 2017;Tereshchenko, Smolnikova, 2020).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As mentioned above, currently, the population frequencies of mutations associated with congenital deficiency of H-ficolin and MASP-2 in Russian populations as a whole, and in populations of indigenous peoples of the Russian Arctic regions in particular, have not been previously studied. Moreover, the previously identified features of the genetic regulation of lectin pathway proteins of complement activation in newborns of the Taimyr Dolgan-Nenets region of the Krasnoyarsk Territory have shown the indigenous populations of the Arctic to be genetically characterized by greater activity of at least two different lectin pathway components of complement activation, i. e. MBL and L-ficolin, indicating a high tone of the lectin pathway of complement activation in general (Smolnikova et al, 2017;Tereshchenko, Smolnikova, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…In the aboriginal populations of both the Nenets and Dolgans/ Nganasans of the Taimyr Dolgan-Nenets region of the Krasnoyarsk Territory, our research group found a decrease in the prevalence of the FCN2 rs7851696 genotype, associated with the low binding capacity of L-ficolin to carbohydrates, as compared with Caucasians of Eastern Siberia. The study results (Smolnikova et al, 2017) showed that the Nenets population has a number of important features compared to the Dolgans and Nganasans, i. e. a much lower prevalence of the T allele for the rs17549193 polymorphism and a higher prevalence of the T allele for the FCN2 rs7851696 polymorphism. We suppose that this genotype can be a genetic marker of the high functional ability of L-ficolin for the Nenets population.…”
mentioning
confidence: 88%
“…В настоящем исследовании нами впервые получены данные о частотах генотипов и гаплотипов гена MBL2 среди коренных народностей, проживающих на территориях Арктической зоны Российской Федерации. Ранее нами была показана большая частота распространенно сти генотипов, ассоциированных с высокой активностью Lфиколина, в арктических популяциях ненцев и долган нганасан, в сравнении с европеоидами Восточной Сибири (Smolnikova et al, 2017). Таким образом, популяции коренных народов Арктики генетически характеризуются большей активностью как минимум двух различающихся компонентов лектинового пути активации комплемента -MBL и Lфиколина.…”
Section: результаты и обсуждениеunclassified
“…Таким образом, по результатам настоящего исследования нами показана большая частота встречаемости MBLвы сокопродуцирующих генетических вариаций в популяциях коренных арктических народностей, проживающих в Таймырском ДолганоНенецком районе Красноярского края. Рассматривая представленные данные в совокупности с ранее опубликованными результатами полиморфизма гена Lфиколина в тех же популяциях (Smolnikova et al, 2017), можно говорить не только о накоплении отдельных генотипов MBL2 и FCN2 в арктических популяциях, но и о большем тонусе лектинового пути активации комплемента в целом. Указанные факты позволяют нам осторожно высказаться о гипотезе селективного популяционного давления в отношении лектинового пути активации комплемента как общего патофизиологического механизма, опосредованного генами MBL2 и FCN2, и, вероятно, ассоциированного с предрасположенностью к некоторым инфекциям.…”
Section: заключениеunclassified
“…Показано, что в легких в наибольшей степени продуцируется H-фиколин, а его комплементсвязывающая способность превышает таковую MBL [10]. Показаны значительные популяционные различия в распределении генотипов гена FCN2, предположительно ассоциированные с его концентрацией и функциональной активностью [37].…”
Section: роль врожденного дефицита/дисфункции коллектинов в предраспоunclassified